The Impact of Organizational Justice on Organizational Performance in View Point of Employee Voice - Parveen, Kaur; Abdul Khaliq, Alvi; Raza Hussain, Lashari; Saif UR, Rehman; Arif, Jawaid (Skripta s.r.o., Česká Republika, 2019)
in an organization’s functions. The main intention of current research is to explore the connection of employee voice with organizational justice and its ultimately impact on organizational performance. Banking sector of Lahore (Pakistan) has been considered as target population. 15 bank’s branches were selected randomly for conducting the research. Overall 220 questionnaires were distributed. 190 questionnaires were returned back and used for analysis. Results demonstrated the direct positive influence of organizational justice on employee voice and organizational performance. Moreover, results showed that the employee voice partially mediates the relationship between organizational justice and organizational performance along with its two dimensions (sales growth and profitability). These results will be very helpful in fostering the efforts of HR specialists towards formulating and embedding the employee’s voice mechanism in service sector.